DOUBLE TUNING OF A DUAL EXTERNAL CAVITY SEMICONDUCTOR LASER FOR BROAD WAVELENGTH TUNING WITH HIGH SIDE MODE SUPPRESSION - Abu-El-Magd, Ali (My University, 2011)
Over the past few years various successful miniaturization attempts of External Cavity Semiconductor Lasers (ECSL) were published. They built upon the rich literature of ECSL configurations that were extensively analyzed and improved upon since the 1960s. This was merged with the microfabrication techniques of 3D structures based on MEMS technology. The main drive for miniaturizing such tunable lasers in the recent past was the huge potential for such devices in all optical networks specifically as signal sources that enable Wavelength Division Multiplexing (WDM).
This thesis compares the different configurations chosen to build tunable lasers using MOEMS technology. Our criteria of comparison include wavelength tuning range, side mode suppression, tuning speed and device dimensions. Designs based on the simple ECSL with a movable external mirror suffered from the tradeoff between tuning range and Side Mode Suppression SMS. To overcome this limitation most designs adopted grating based tuning using the Littrow or Littman/Metcalf configurations. These configurations allow for much better tuning results but don’t lend themselves easily to miniaturization. The grating based devices were bulky and quite complicated to realize.
We propose the adoption of the Zhu/Cassidy double external cavity configuration. It retains the simplicity of the single external mirror configuration along with the tuning range and the SMS of including multiple tuning elements. In its original form this configuration suffered from mode hopping within the tuning range. Thorough simulation, design and experimental evidence is presented in this work to show that by extending the configuration to allow full control over both optical tuning elements this drawback can be eliminated.
Our proposed design would reduce the form factor to < 300μm x 200μm x 200μm. The voltage required to tune through all the modes is < 40V and the resonant frequency of the mirror is in the 10s of MHz order of magnitude. When coupled with a multimode laser of a sufficiently broad lasing profile this setup should enable a tuning range > 72nm with a SMS >20dB.
Keywords: tunable lasers; external cavity lasers; MEOMS; MEMS; dual external cavity; Electromagnetics and photonics; Electronic Devices and Semiconductor Manufacturing; Engineering Physics; Nanotechnology fabrication; Optics; Electromagnetics and photonics